Street Vendors, Spatial Distribution, and Public Perception in Tangerang City - Medtry; Rizka Dwi Apriani; Forina Lestari; Kusmalinda Madjid; Riana Garniati Rahayu (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
Street vendors are an essential element of the urban informal economy, significantly enhancing local livelihoods while frequently generating spatial and regulatory issues in public areas. This study analyses the geographical patterns, activity features, and stakeholder perspectives of street vendors along the Moh Toha Corridor in Tangerang City, Indonesia. The corridor functions as a principal commercial and transportation route linking the city centre to adjacent industrial and residential zones. A descriptive quantitative methodology was employed, integrating field observations, questionnaire surveys, and interviews with 40 participants, comprising vendors, pedestrians, and landowners. Spatial mapping was performed to discern vendor concentration patterns, while perception analysis assessed public views towards street vending activities. The results indicate that the distribution of street vendors adheres to a linear-agglomeration pattern, predominantly situated in high-traffic zones such as intersections, shopfronts, and industrial sites. Most vendors work from morning till evening, offering food, beverages, fruits, and everyday goods from portable kiosks and tents that often obstruct pedestrian pathways. The presence of street vendors bolsters local economic vitality and offers affordable commodities for workers and residents; nevertheless, it also leads to conflicts in space utilisation, resulting in diminished pedestrian comfort, visual disarray, and traffic congestion. Stakeholder perceptions reveal that 82.5% of respondents advocate for spatial reorganisation while preserving vendors' livelihoods. The study suggests that inclusive spatial management via zoning, allocation of designated vending areas, and inter-agency coordination is crucial for reconciling urban order with economic informality in Tangerang's public spaces.